PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN UMKM DI KOTA KENDARI - Dzulfikri Azis Muthalib (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the effect of brand image and product quality on customer loyalty of Micro, Small, and Medium Enterprises (MSMEs) in Kendari City, Southeast Sulawesi. The study employs a quantitative approach using a survey method. Data were collected from 96 respondents who are MSME customers, selected through purposive sampling. Data collection was conducted using a structured questionnaire, and the research instruments were tested for validity and reliability prior to further analysis. Hypothesis testing was performed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that brand image and product quality have a positive and significant effect on customer loyalty. The findings also reveal that product quality plays a more dominant role than brand image in shaping customer loyalty. These results suggest that MSMEs in Kendari City need to prioritize continuous improvement and consistency in product quality, supported by strengthening brand image through effective marketing communication, in order to create sustainable customer loyalty